Red hot rancher - Child, Maureen (Harlequin Enterprises Limited, 2019)
One look at Emma Williams and rich rancher Caden Hale knows he hasn<U+2019>t forgiven her for leaving Montana. She<U+2019>s back with a baby<U+2014>the family Caden thought would be theirs. Has Emma really changed? Maybe. But one thing hasn<U+2019>t changed<U+2014>the incredible heat between them! But after his trust was shattered, can they really pick up where they ended?